Anticorrosive and abrasion resistant nickel-based alloy

A nickel-based alloy with tailored compositions addresses the challenge of balancing wear and corrosion resistance, offering a durable and resistant hardfacing layer for applications in abrasive and corrosive conditions.

JP2025000915AInactive Publication Date: 2025-01-07OERLIKON METCO (US) INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024173010
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-10-26
Filing Date
2024-10-02
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Current materials fail to provide a balance between wear resistance and corrosion resistance, leading to material defects such as cracking and reduced service life in applications involving abrasive and corrosive environments.

Method used

A nickel-based alloy with specific compositions of C, Cr, Mo, Nb, and Ti, formulated to form hard phases with high Vickers hardness and a corrosion-resistant matrix, suitable for processes like plasma transferred arc (PTA) and laser cladding, providing a wear-resistant and corrosion-resistant hardfacing layer.

Benefits of technology

The alloy achieves high abrasion resistance with minimal cracking and low porosity, along with corrosion rates below 1 mpy in electrolytes, making it suitable for harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000915000001_ABST
    Figure 2025000915000001_ABST
Patent Text Reader

Abstract

To provide an anticorrosive and abrasion resistant nickel-based alloy that can serve as a proper raw material for hardfacing processing, such as plasma transferred arc (PTA), laser cladding hardfacing processing including high-speed laser cladding, and high-speed frame (HVOF) thermal spraying.SOLUTION: Provided is a raw material containing Ni, 0.5-2 wt.% of C, 10-30 wt.% of Cr, 5.81-18.2 wt.% of Mo, and 2.38-10 wt.% of Nb+Ti.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [Incorporation by reference of any prior application] This application is a joint venture between the US Provisional Patent Application No. 2018 / 10 / 26 entitled "Corrosion-Resistant and Wear-Resistant Nickel-Based Alloy." This application claims priority to U.S. Patent Application Serial No. 62 / 751,020, entitled "Invention of the Invention," all of which are hereby incorporated by reference in their entirety. all of which are incorporated herein by reference.

[0002] [Technical field] Embodiments of the present disclosure generally relate to plasma transferred arc (PTA), high speed laser Laser cladding hardfacing processes, including laser cladding, and high speed f A suitable raw material for hardfacing processes such as flame (HVOF) spraying and other thermal spraying processes The present invention relates to a nickel-based alloy. [Background technology]

[0003] [Description of Related Art] Abrasive and corrosive wear are applications involving sand, rock, or other hard media that wear away the surface. This is a major problem for operators in applications where significant wear occurs. High hardness materials are used to prevent material failure due to excessive wear. are typically referred to as hard precipitates that make the material less susceptible to wear and increase the bulk hardness of the material. These materials often contain carbides and / or borides in various welding processes. It is applied as a coating known as a hardfacing by chemical processing or directly Cast into parts.

[0004] Another major problem for operators is corrosion. In highly corrosive applications, typically For these, use high chromium soft nickel-based or stainless steel type materials. In this type of application, cracks in the build-up layer should not be present as they will result in corrosion of the underlying substrate. Not good.

[0005] Currently, the use of either wear-resistant or corrosion-resistant materials does not meet both requirements. This is common because there are few alloys that satisfy the above criteria. Current materials are often The required service life may not be obtained, or the carburizing agent may be used to increase the wear resistance, which may lead to cracking. This requires the addition of byde. Summary of the Invention

[0006] In this specification, the weight percentages are Ni, C: 0.5-2, Cr: 10-30, and Mo: 5. An embodiment of the raw material including Nb+Ti: 81-18.2, Nb+Ti: 2.38-10 is disclosed.

[0007] In some embodiments, the raw material contains, by weight, C: about 0.8 to about 1.6, Cr: about 14 In some embodiments, the compound may further include Mo: about 8 to about 16. The raw materials are, by weight, C: about 0.84 to about 1.56, Cr: about 14 to about 26, Mo: about 8 It may further include Nb+Ti: about 4.4 to about 15.6, and Nb+Ti: about 4.2 to about 8.5. In some embodiments, the raw material contains, in weight percent, C: about 8.4 to about 1.56, Cr: about 14 to about 1.56, 26, Mo: about 8.4 to about 15.6, Nb: about 4.2 to about 7.8, and Ti: about 0.3 In some embodiments, the ingredients may further comprise, in weight percent, 0.5 to about 0.65. , C: about 1.08 to about 1.32, Cr: about 13 to about 22, Mo: about 10.8 to about 13.2 and Nb: about 5.4 to about 6.6. The raw materials were, by weight, C: about 1.2, Cr: about 20, Mo: about 12, Nb: about 6, and Ti. : about 0.5.

[0008] In some embodiments, the feedstock is a powder. In some embodiments, the feedstock is a wire. In some embodiments, the feedstock is a combination of wire and powder.

[0009] Also, embodiments of hardfacing layers formed from the feedstock materials as disclosed herein. is disclosed herein.

[0010] In some embodiments, the hardfacing layer comprises 1.0 mole percent or more of total 5 mole percent or more of SiO. Hard phases with a Vickers hardness of 00 or more, and a combined total of chromium and molybdenum of 20% or more by weight. butene, separated hypereutectic hard phases which are 50 mol % or more of the total hard phase fraction in total, 0.33 to 3 WC / Cr3C2 ratio, 250mm 3 ASTM G65A abrasion loss of less than 650 The Vickers hardness of the nickel substrate may be above 1000.

[0011] In some embodiments, the hardfacing layer has a Vickers hardness of 750 or greater. In some embodiments, the hardfacing layer may have a thickness of about 100 mm per square inch. exhibiting no more than two cracks, a bond strength of 9,000 psi or greater, and a porosity of 2% or less by volume. In some embodiments, the hardfacing layer may have 0.5% by volume or more. In some embodiments, the hardfacing layer may have a porosity of less than 100%. Corrosion rate of 1mpy or less in 28% CaCl2 electrolyte, pH=9.5 environment In some embodiments, the hardfacing layer is made of 28% CaCl 2. It has a corrosion rate of less than 0.4mpy in an electrolyte pH=9.5 environment. In some embodiments, the hardfacing layer is compliant with G-59 / G-61. The corrosion rate was less than 0.1 mpy in a 3.5% sodium chloride solution for 16 hours. In some embodiments, the hardfacing layer may comprise G-59 / G -61 in 3.5% sodium chloride solution for 16 hours at 0.08 mpy or less The corrosion rate of the alloy may be less than that of the alloy.

[0012] In some embodiments, the nickel matrix is ​​defined as Ni:balance, X>20 wt.%. Compared with corrosion-resistant alloys, it has 80% or more of base material similarity, and X is Cu, Cr, or Mo. In some embodiments, the corrosion resistant alloy comprises at least one of Incon El 625, Inconel 622, Hastelloy C2 76, HastelloyX, and Monel® 400. can be.

[0013] In some embodiments, the hardfacing layer is formed by hydraulic cylinders, tension lines, The present invention can be applied to turbines, mud motor rotors, or oil field component applications.

[0014] Further disclosed herein are embodiments of a feedstock comprising nickel, the feedstock being thermodynamically hard phases having a Vickers hardness of 1,000 or more, which total at least 5 mole percent under equilibrium conditions; Compared with known corrosion-resistant nickel alloys, it is characterized by having 80% or more similarity to the base material. The method is configured to form a corrosion resistant base material to which a corrosion resistant coating can be applied.

[0015] In some embodiments, the known corrosion resistant nickel alloy has the composition Ni: balance, X>2 0% by weight, where X represents at least one of Cu, Cr, or Mo. vinegar.

[0016] In some embodiments, the raw material may be a powder. The powder can be produced by a spray process. In some embodiments, the powder is agglomerated. The ceramic can be fabricated by a bonding and sintering process.

[0017] In some embodiments, the corrosion resistant base material has a combined total chromium content of 20% or more by weight. and molybdenum. Under chemical equilibrium conditions, the corrosion-resistant base material contains a total of 50 mol % or more of the total hard phase fraction. It can be characterized as having a hypereutectic hard phase.

[0018] In some embodiments, known corrosion resistant nickel alloys include Inconel 625, In conel622, HastelloyC276, HastelloyX, and Mone The compound may be selected from the group consisting of: l400.

[0019] In some embodiments, the raw materials are C: 0.84-1.56, Cr: 14-26, Mo : 8.4-15.6, Nb: 4.2-7.8, and Ti: 0.35-0.65 In some embodiments, the raw material has a B content of about 2.5 to about 5.7 and a Cu content of about 9. In some embodiments, the feedstock may further include Cr: about 7.8 to about 23. may further include up to about 14.5.

[0020] In some embodiments, under thermodynamic equilibrium conditions, the corrosion-resistant base material has a total of 50 moles. % or more of hard phase and a liquidus temperature of 1550 K or less. can be done.

[0021] In some embodiments, the raw materials are Monel and at least one of WC or Cr3C2. and mixtures thereof.

[0022] In some embodiments, the feedstock comprises, by weight, 75-85% WC+15-25% M onel, 65~75%WC+25~35%Monel, 60~75%WC+25~40 %Monel, 75~85%Cr3C2+15~25%Monel, 65~75%Cr3 C2+25~35%Monel, 60~75%Cr3C2+25~40%Monel, 7 5~85%WC / Cr3C2+15~25%Monel, 65~75%WC / Cr3C2 +25~35%Monel, and 60~75%WC / Cr3C2+25~40%Monel l.

[0023] In some embodiments, the WC / Cr3C2 ratio of the corrosion-resistant matrix is ​​0.02 by volume. In some embodiments, the thermal spray feedstock may include a wire. In some embodiments, the thermal spray feedstock may include a combination of wire and powder.

[0024] Also, embodiments of hardfacing layers formed from the feedstock materials as disclosed herein. is disclosed herein.

[0025] In some embodiments, the hardfacing layer is 250 mm 3 Less than ASTM G 65A wear loss, and the hard facing layer is treated with PTA or laser cladding In some embodiments, the molded article may contain no more than two cracks per square inch when formed from the molded article. In this study, the hardfacing layer was placed in an environment of 28% CaCl2 electrolyte, pH=9.5. It can include impermeable HVOF coatings that exhibit corrosion rates of less than 1mpy in .

[0026] In some embodiments, the hardfacing layer has a Vickers hardness of 650 or greater, and When the hardfacing layer is formed by HVOF thermal spraying, the hardfacing layer is heated to 9,000 psi or more. Adhesive properties may also be included.

[0027] In some embodiments, the hardfacing layer is formed by hydraulic cylinders, tension lines, The present invention can be applied to turbines, mud motor rotors, or oil field component applications.

[0028] In some embodiments, the hardfacing layer has a Vickers hardness of 750 or greater, and When the hardfacing layer is formed by HVOF thermal spraying, the hardfacing layer is preferably 2% by volume or less. may contain less than 0.5% porosity. [Brief description of the drawings]

[0029] [Figure 1] FIG. 1 shows a phase mole fraction versus temperature diagram for alloy P82-X6 showing the mole fractions of the phases present in the alloy at various temperatures. [Diagram 2] FIG. 2 shows a phase mole fraction diagram versus temperature for alloy P76-X23 showing the mole fractions of the phases present in the alloy at various temperatures. [Diagram 3] FIG. 3 shows an SEM image of one embodiment of alloy P82-X6, which includes a hard phase, a hypereutectic hard phase, and a matrix. [Figure 4]FIG. 4 shows an optical microscope image of P82-X6 laser welded from gas atomized powder in Example 1, parameter set 1. [Diagram 5] FIG. 5 shows SEM images of the gas atomized powder 501 and the resulting coating 502 of the P76-X24 alloy in Example 2. [Figure 6] FIG. 6 shows SEM images of HVOF coatings deposited from the agglomerated and sintered powder of WC / Cr3C2+Ni alloy in Example 3, specifically a mixture of 80 wt. % WC / Cr3C2 (50 / 50 vol.%) mixed with 20 wt. % Monel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Embodiments of the present disclosure include, but are not limited to, hardfacing / hardbanding. hardfacing / hardbanding materials, used to make such hardfacing / hardbanding materials Alloy or powder composition for forming hardfacing / hardbanding material and mixing or combining these hardfacing / hardbanding materials. This includes parts or substrates protected by hardfacing / hardbanding materials. nothing.

[0031] In certain applications, it forms a metal layer that is highly resistant to abrasive and corrosive wear and does not corrode. It may be advantageous to make the material less susceptible to wear and corrosion. The present invention discloses an embodiment of a nickel-based alloy that has been developed. Industries that could benefit include marine applications, coatings in the power industry, oil and gas applications, Includes coatings for glass manufacturing.

[0032] In some embodiments, the alloys disclosed herein may further be modified to improve performance. Inconel® and Hastelloy®, which also contain other elements The alloys are designed to form microstructures with matrix chemistries similar to some known alloys such as For example, carbides can be added to the matrix of the material. It is possible to improve corrosion resistance and abrasion resistance.

[0033] In the complex alloy space, it is possible to simply remove an element or replace it with another and achieve equivalent results. It is necessary to understand that this is not possible.

[0034] In some embodiments, the nickel-based alloy as described herein is Laser cladding including phased arc (PTA) and high speed laser cladding For thermal spraying processes, including hardfacing and high velocity fuel (HVOF) thermal spraying However, the disclosure is not so limited. The present invention relates to the manufacture of nickel-based alloys into cored wires for hardfacing processing. and Welding of Nickel-Based Wires and Powders with Wire-Fed and Short Wavelength Lasers and a method.

[0035] The term alloy refers to the chemical composition of the powders used to form the metal components, the powders themselves, The chemical composition of the melt used to form the cast component, the melt itself, and the melt strength after cooling Metallic components formed by heating, sintering, and / or deposition of powders, including the composition of the metallic components In some embodiments, the term alloy may refer to a composition of the disclosed powders. Chemical composition, powder itself, raw material itself, wire, wire containing powder, combination of wires Compositions of metal parts formed by heating and / or deposition of powders or other techniques; It can also refer to metal members.

[0036] In some embodiments, for use as a feedstock for welding or other processes. Alloys manufactured into solid or cored wires (powder-containing sheath) are herein It can be described by its specific chemical composition. For example, the wire can be used for thermal spraying. Additionally, the compositions disclosed below can be used in the manufacture of single wires or multiple wires (2, 3, 4 , or 5 wires, etc.

[0037] In some embodiments, the alloy may be adapted to form a thermal spray coating, such as an HVOF alloy. In some embodiments, the alloy may be applied to the weld overlay by a thermal spray process. In some embodiments, the alloy can be applied as a layer. It can be applied as a thermal spray layer or as a weld build-up layer.

[0038] [Metal alloy composition] In some embodiments, the product, such as the composition of matter disclosed herein, comprises Ni and, in weight percent, B: 0 to 4 (or about 0 to about 4); C: 0 to 9.1 (or about 0 to about 9.1); Cr: 0 to 60.9 (or about 0 to about 60.9); Cu: 0 to 31 (or about 0 to about 31); Fe: 0 to 4.14 (or about 0 to about 4.14); Mn: 0 to 1.08 (or about 0 to about 1.08); Mo: 0 to 10.5 (or about 0 to about 10.5); Nb: 0 to 27 (or about 0 to about 27); Si: 0 to 1 (or about 0 to about 1); Ti: 0 to 24 (or about 0 to about 24); and W: 0 to 12 (or about 0 to about 12).

[0039] In some embodiments, the product, such as the composition of matter disclosed herein, comprises Ni and, in weight percent, C: 0.5 to 2 (or about 0.5 to about 2); Cr: 10-30 (or about 10-about 30); Mo: 5 to 20 (or about 5 to about 20); and It may contain Nb+Ti:2 to 10 (or about 2 to about 10).

[0040] In some embodiments, the product, such as the composition of matter disclosed herein, comprises Ni and, in weight percent, C: 0.8 to 1.6 (or about 0.8 to about 1.6); Cr: 14-26 (or about 14 to about 26); Mo: 8 to 16 (or about 8 to about 16); and It may contain Nb+Ti:2 to 10 (or about 2 to about 10).

[0041] In some embodiments, the product, such as the composition of matter disclosed herein, comprises Ni and, in weight percent, C: 0.84 to 1.56 (or about 0.84 to about 1.56); Cr: 14-26 (or about 14 to about 26); Mo: 8.4 to 15.6 (or about 8.4 to about 15.6); and Nb+Ti: 4.2 to 8.5 (or about 4.2 to about 8.5).

[0042] In some embodiments, the product, such as the composition of matter disclosed herein, comprises Ni and, in weight percent, C: 0.84 to 1.56 (or about 0.84 to about 1.56); Cr: 14-26 (or about 14 to about 26); Mo: 8.4 to 15.6 (or about 8.4 to about 15.6); Nb: 4.2 to 7.8 (or about 4.2 to about 7.8); and Ti: 0.35 to 0.65 (or about 0.35 to about 0.65).

[0043] In some embodiments, the product, such as the composition of matter disclosed herein, comprises Ni and, in weight percent, C: 1.08 to 1.32 (or about 1.08 to about 1.32); Cr: 13-22 (or about 13 to about 22); Mo: 10.8 to 13.2 (or about 10.8 to about 13.2); and Nb: 5.4 to 6.6 (or about 5.4 to about 6.6).

[0044] In some embodiments, the product, such as the composition of matter disclosed herein, comprises Ni and, in weight percent, C: 0.5 to 2 (or about 0.5 to about 2); Cr: 10-30 (or about 10-about 30); Mo: 5.81 to 18.2 (or about 5.81 to about 18.2); and Nb+Ti: 2.38 to 10 (or about 2.38 to about 10).

[0045] In some embodiments, the product, such as the composition of ingredients as disclosed herein, is The percentages may include one of the following: C: 0.5, Cr: 24.8, Mo: 9.8, Ni: balance (or C: approx. 0.5, Cr: approx. 24.8, Mo: approx. 9.8, Ni: remaining); C:0.35~0.65, Cr:17.3~32.3, Mo:6.8~12.7, Ni: Remaining amount (or C: approx. 0.35 to approx. 0.65, Cr: approx. 17.3 to approx. 32.3, Mo: approx. 6. 8 to about 12.7, Ni: remaining amount); C:0.45~0.55, Cr:22.3~27.3, Mo:8.8~10.8, Ni: Remaining amount (or C: approx. 0.45 to approx. 0.55, Cr: approx. 22.3 to approx. 27.3, Mo: approx. 8. 8 to about 10.8, Ni: remaining amount); C: 0.8, Cr: 25, Mo: 14, Ni: balance (or C: approx. 0.8, Cr: approx. 25, Mo: approx. 14, Ni: remaining); C:0.56~1.04, Cr:17.5~32.5, Mo:9.8~18.2, Ni: Remaining amount (or C: approx. 0.56 to approx. 1.04, Cr: approx. 17.5 to approx. 32.5, Mo: approx. 9. 8 to about 18.2, Ni: remaining amount); C:0.7~0.9, Cr:22.5~27.5, Mo:12.6~15.4, Ni: Residual Amount (or C: about 0.7 to about 0.9, Cr: about 22.5 to about 27.5, Mo: about 12.6 to about Approximately 15.4, Ni: remaining amount); C: 1.2, Cr: 24, Mo: 14, Ni: balance (or C: approx. 1.2, Cr: approx. 24, Mo: approx. 14, Ni: remaining); C:0.84~1.56, Cr:16.8~31.2, Mo:9.8~18.2, Ni: Remaining amount (or C: approx. 0.84 to approx. 1.56, Cr: approx. 16.8 to approx. 31.2, Mo: approx. 9. 8 to about 18.2, Ni: remaining amount); C:1.08~1.32, Cr:21.6~26.4, Mo:12.6~15.4, Ni : Remaining amount (or C: approx. 1.08 to approx. 1.32, Cr: approx. 21.6 to approx. 26.4, Mo: approx. 2.6 to about 15.4, Ni: remaining amount); C: 1.2, Cr: 20, Mo: 12, Nb: 6, Ti: 0.5, Ni: balance (or C: 1.2, Cr: approx. 20, Mo: approx. 12, Nb: approx. 6, Ti: approx. 0.5, Ni: balance); C:0.84~1.56, Cr:14~26, Mo:8.4~15.6, Nb:4.2~ 7.8, Ti: 0.35-0.65, Ni: balance (or C: approx. 0.84-approx. 1.56, C r: about 14 to about 26, Mo: about 8.4 to about 15.6, Nb: about 4.2 to about 7.8, Ti: Approximately 0.35 to approximately 0.65, Ni: remaining amount); C:1.08~1.32, Cr:18~22, Mo:10.8~13.2, Nb:5.4 ~6.6, Ti: 0.45~0.55, Ni: balance (or C: about 1.08~about 1.32, Cr: about 18 to about 22, Mo: about 10.8 to about 13.2, Nb: about 5.4 to about 6.6, T i: approx. 0.45 to approx. 0.55, Ni: remaining amount); C: 1.6, Cr: 18, Mo: 14, Nb: 6, Ni: balance (or C: approx. 1.6, Cr : approx. 18, Mo: approx. 14, Nb: approx. 6, Ni: remaining amount); C:1.12~2.08, Cr:12.6~23.4, Mo:9.8~18.2, Nb: 4.2 to 7.8, Ni: balance (or C: approx. 1.12 to approx. 2.08, Cr: approx. 12.6 to approx. 23.4, Mo: approx. 9.8 to approx. 18.2, Nb: approx. 4.2 to approx. 7.8, Ni: balance); C:1.44~1.76, Cr:16.2~19.8, Mo:12.6~15.4, Nb : 5.4 to 6.6, Ni: remaining amount (or C: about 1.44 to about 1.76, Cr: about 16.2 to 19.8, Mo: 12.6 to 15.4, Nb: 5.4 to 6.6, Ni: balance) .

[0046] In some embodiments, the product, such as the composition of matter disclosed herein, comprises Ni and, in weight percent, C: 1.4, Cr: 16, Fe: 1.0, Mo: 10, Nb: 5, Ti: 3.8 (or C: approx. 1.4, Cr: approx. 16, Fe: approx. 1.0, Mo: approx. 10, Nb: approx. 5, Ti: approx. 3.8); B: 3.5, Cu: 14 (or B: about 3.5, Cu: about 14); B: 2.45 to 4.55 (or about 2.45 to about 4.55), Cu: 9.8 to 18.2 (or about 9.8 to about 18.2); B: 3.15-3.85 (or about 3.15-about 3.85), Cu: 12.6-15. 4 (or about 12.6 to about 15.4); B: 4.0, Cr: 10, Cu: 16 (or B: about 4.0, Cr: about 10, Cu: about 16); B: 2.8 to 5.2 (or about 2.8 to about 5.2), Cr: 7 to 13 (or about 7 to about 13), Cu: 11.2 to 20.8 (or about 11.2 to about 20.8); B: 3.6 to 4.4 (or about 3.6 to about 4.4), Cr: 9 to 11 (or about 9 to about 11), Cu: 14.4 to 17.6 (or about 14.4 to about 17.6); or C: 1.2, Cr: 20, Mo: 12, Nb: 6, Ti: 0.5 (or C: about 1.2, C r: about 20, Mo: about 12, Nb: about 6, Ti: about 0.5).

[0047] In some embodiments, the product, such as the composition of ingredients as disclosed herein, is Agglomerated and sintered in percent 75~85%WC+15~25%Monel; 65~75%WC+25~35%Monel; 60~75%WC+25~40%Monel; 75~85%Cr3C2+15~25%Monel; 65~75%Cr3C2+25~35%Monel; 60~75%Cr3C2+25~40%Monel; 60~85%WC+15~40%Ni30Cu; 60~85%Cr3C2+15~40%Ni30Cu; 75~85%(50 / 50vol%)WC / Cr3C2+15~25%Monel; 75~85%(50 / 50vol%)WC / Cr3C2+25~35%Monel; 75~85%WC / Cr3C2+15~25%Monel; 75~85%WC / Cr3C2+25~35%Monel; or It may contain a mixture of 60-90% hard phase + 10-40% Monel alloy.

[0048] In the above, the hard phase is tungsten carbide (WC) and / or chromium carbide. Monel® is one or more of the following: C, Mn, S, Si, 20-40 wt. % Cu or less with known impurities including but not limited to Fe More preferably, the target composition should have a typical chemical tolerance of 28-34 wt.% Cu. The composition is a nickel-copper alloy with the remaining Ni being 30% by weight and Cu being 30% by weight. Thus, embodiments of the present disclosure do not include tungsten carbide and / or chromium carbide. Tungsten carbide is generally made up of the following components: W: Remainder, In some embodiments, tungsten carbide is represented by 4 to 8 wt.% C. Generally, it can be expressed as the blending component W: balance, 1.5 wt% C.

[0049] In some embodiments having 60-85% WC+Ni30Cu, the product has a weight percent In St. Ni: 10.5 to 28 (or about 10.5 to about 28); Cu: 4.5 to 12 (or about 4.5 to about 12); C: 3.66 to 5.2 (or about 3.66 to about 5.2); W: 56.34 to 79.82 (or approximately 56.34 to approximately 79.82).

[0050] In some embodiments having 60-85% Cr3C2+Ni30Cu, the product is heavy In percent by volume, Ni: 10.5 to 28 (or about 10.5 to about 28); Cu: 4.5 to 12 (or about 4.5 to about 12); C: 7.92 to 11.2 (or about 7.92 to about 11.2); W: 52.1 to 73.78 (or about 52.1 to about 73.79).

[0051] Thus, the above description of the raw materials is expressed by the simple chemical formula Ni30Cu (with the given ratios). (As shown in Fig. 1) The known alloy tungsten carbide with the simple chemical formula Monel This indicates mechanical mixing. During this entire process, many particles stick together and form new particles. In each case, the agglomerated particles are dispersed in the ratios shown. It consists of:

[0052] Table 1 lists a number of experimental alloys along with their compositions in weight percent. [Table 1]

[0053] In some embodiments, the P76 alloy is a thermal spray alloy and the P82 alloy is a weld overlay alloy (P TA or laser, etc. However, the disclosure is not so limited. For example, any of the compositions disclosed herein may be used in plasma transferred Laser cladding hardfacing, including arc (PTA), high speed laser cladding Hardfacing, such as facing, and thermal spraying, including high velocity fuel (HVOF) thermal spraying. This may be suitable for processing.

[0054] In Table 1, all values ​​can also be expressed as "about" values. For example, P In 82-X1, Ni is 59 (or approximately 59).

[0055] In some embodiments, the disclosed compositions can be applied to wires / powders, coatings, or other metals. The support may be a material, a component, or both.

[0056] The disclosed alloys may contain up to 100% by weight of the above elemental components in total. In embodiments, the alloy may include, but is not limited to, the elements listed above. The composition may be selected from the group consisting of, or may consist essentially of, the elements listed above. In some embodiments, the alloy may be present in an amount of 2% by weight or less, 1% by weight or less, % by weight or less, 0.5% by weight (or about 0.5% by weight) or less, 0.1% by weight (or about 0.1% by weight or less, or 0.01% by weight (or about 0.01% by weight) or less, can include any range of impurities between any of these values. Impurities can be It can be included in the alloy because it is included in the raw material components by being introduced in the process. It can be understood as an element or a composition.

[0057] Furthermore, the Ni content specified in all of the compositions described in the preceding paragraphs is or, if Ni is provided as the balance, the balance of the composition is Ni and other elements. In some embodiments, the balance consists essentially of Ni. and may contain incidental impurities.

[0058] [Thermodynamic conditions] In some embodiments, an alloy can be characterized by its equilibrium thermodynamic condition. In some embodiments, the alloys are characterized as meeting some of the described thermodynamic conditions. In some embodiments, the alloy can be characterized as being in any of the thermodynamic conditions described. can be characterized as satisfying all of the above.

[0059] The first thermodynamic condition is related to the total concentration of ultrahard particles in the microstructure. As the mole fraction increases, the bulk hardness of the alloy may increase, and therefore the wear resistance may also increase. For the purposes of this disclosure, ultra-hard particles are 1000 Bi. It can be defined as a phase that exhibits a hardness of 1000 Vickers or more (or about 1000 Vickers or more). The total concentration of ultra-hard particles is 1000 Vickers (or approximately 1000 Vickers) hardness. and the alloy is thermally stable at or near 1500 K. It can be defined as the total mole percentage of all phases that are mechanically stable.

[0060] In some embodiments, the ultra-hard particle fraction is 3 mol % or more (or about 3 mol % or more). ), 4 mol% or more (or about 4 mol% or more), 5 mol% or more (or about 5 mol% or more) ), 8 mol% or more (or about 8 mol% or more), 10 mol% or more (or about 10 mol% or more), 12 mol % or more (or about 12 mol % or more), or 15 mol % or more (if or about 15 mol% or more), 20 mol% or more (or about 20 mol% or more), 30 mol% or more or above (or about 30 mol % or more), 40 mol % or more (or about 40 mol % or more), 50 mol% or more (or about 50 mol% or more), 60 mol% or more (or about 60 mol% or more) ), or any range between any of those values.

[0061] In some embodiments, the ultra-hard particle fraction may vary depending on the intended alloy processing. For example, in a thermal spray alloy, the hard particle fraction is 40-60 mole % (or about 40-60 mole %) ) Laser, plasma transferred arc, or other wire welding. In alloys used for welding by application, the hard particle phase fraction is 15-30 mole percent. (or about 15 to about 30 mol %).

[0062] The second thermodynamic condition concerns the amount of hypereutectic hard phase that forms in the alloy. , a hard phase that begins to form at temperatures above the eutectic point of the alloy. The eutectic point of these alloys is F This is the temperature at which the CC matrix begins to form.

[0063] In some embodiments, the hypereutectic hard phase comprises a total of about 100% of the total hard phase present in the alloy. 40 mol% or more (or about 40% or more), 45 mol% or more (or about 45% or more), 50 mol% or more (or about 50% or more), 60 mol% or more (or about 60% or more), 70 mol% or more (or about 70% or more), 75 mol% or more (or about 75% or more), or 80 mole % or more (or about 80% or more), or any value therebetween. This falls within the scope of intent.

[0064] The third thermodynamic condition concerns the corrosion resistance of the alloy. The corrosion resistance of nickel-based alloys is It increases as the weight percentage of chromium and / or molybdenum present in the material increases. This third thermodynamic condition is the FCC matrix at 1500K (or about 1500K). The total weight percent of chromium and molybdenum is evaluated.

[0065] In some embodiments, the total weight percent of chromium and molybdenum in the base material is 15 weight percent. % or more (or about 15% by weight or more), 18% by weight or more (or about 18% by weight or more), 20% by weight or more (or about 20% by weight or more), 23% by weight or more (or about 23% by weight or more), 25% by weight or more (or about 25% by weight or more), 27% by weight or more (or about 2 7% by weight or more), or 30% by weight or more (or about 30% by weight or more), or any other Any range between these values.

[0066] The fourth thermodynamic condition relates to the base metal chemistry of the alloy. For example, Inconel622, Inconel625, Inconel686, Haste Similar to known alloys such as lloyC276, HastelloyX, or Monel400 It may be beneficial to maintain similar matrix chemistry. In order to maintain a similar base metal chemistry to known alloys, the alloys were preformed at 1300K. The chemical composition of the alloy was compared to that of a known alloy. Such a comparison is called base metal approximation. Such superalloys are composed of the following components in weight percent: Ni: balance, Cr: 15-25, Mo: 8- It can be represented by 20. Inconel622 Cr:20~22.5, Mo:12.5~14.5, Fe:2~ 6, W: 2.5~3.5, Ni: remaining Inconel625 Cr:20~23, Mo:8~10, Nb+Ta:3.15~4 .15, Ni: Remaining Inconel686 Cr:19~23, Mo:15~17, W:3~4.4, Ni: Remaining HastelloyC276 Cr:16, Mo:16, Fe:5, W:4, Ni:Remaining HastelloyX Cr:22, Fe:18, Mo:9, Ni:Remaining Monel Cr: 28~34, Ni: remaining amount

[0067] In some embodiments, the base metal closeness is 50% (or less) of any of the above-mentioned known alloys. is about 50%) or more, 55% (or about 55%) or more, 60% (or about 60%) or more , 70% (or about 70%) or more, 80% (or about 80%) or more, 85% (or The approximate energy is about 85% or more, or 90% or more. This can be determined in a number of ways, including by electron dispersion analysis (EDS).

[0068] The following formula calculates the similarity or closeness of a model alloy base material to an alloy with known corrosion resistance. A value of 100% means exact agreement between the compared elements. Taste.

number

[0069] A fifth thermodynamic condition can be used to determine whether an alloy is suitable for gas atomization manufacturing processes. The liquidus temperature refers to the liquidus temperature of an alloy at which it is possible to melt it. The liquidus temperature is the lowest temperature at which an alloy is still 100% liquid. Generally, a lower liquidus temperature corresponds to increased stability of the gas atomization process. In some embodiments, the liquidus temperature of the alloy is 1850 K (or about 1850 K) or less. In some embodiments, the liquidus temperature of the alloy may be 1600 K (or In some embodiments, the liquidus temperature of the alloy may be less than or equal to about 1600 K. , can be 1450K (or about 1450K) or less.

[0070] The thermodynamic behavior of alloy P82-X6 is shown in Figure 1. The diagram shows the More than 5% hypereutectic FCC carbides 101 in nickel matrix 103 101 shows the FCC carbide fraction as a function of temperature, which forms a separate hypereutectic phase. The 102 contains FCC carbide in addition to M6C carbide, and is rated at 1300K. Thus, the hypereutectic hard phases make up 50% of the total hard phase of the alloy. Exceeds. 103 refers to the alloy's base material, which is FCC_L12 nickel base. Alloy 103 The parent material similarity is greater than 60% when compared to Inconel625.

[0071] M6C type carbides also precipitate at low temperatures, with a total carbide content of about 15 mol % at 1300 K. The carbide content is 12.6% FCC carbide, 2.4% M6C carbide. FCC carbides refer to the separated carbides in the alloy and also to the It constitutes the majority (>50%) of the total carbides. The arrows are for insertion into the matrix approximation equation. Specifically, the point is to extract the composition of the FCC_L12 base material. The volume fraction of all hard phases exceeds 5 mol%, while the carbide fraction does not exceed 50%. The remaining FCC_L1 2 The matrix phase has a similarity of more than 60% to Inconel625.

[0072] In this calculation, although not shown in Figure 1, the chemical composition of the FCC_L12 base metal phase The chemical composition of the base metal is 18% by weight Cr, 1% by weight Fe, 9% by weight Mo, and The chemical composition of the base material of P82-X6 is P82-X6 It can be seen that the bulk chemical composition of P82-X6 is completely different from that of Incon. It is designed to have similar corrosion performance to Inconel625. The approximateness to the base material is 87%.

[0073] The thermodynamic behavior of alloy P76-X23 is shown in Figure 2. The diagram is for a nickel-based alloy of 20 1 represents a material that precipitates eutectic Ni3B203. indicates the liquidus temperature of the alloy, which is lower than 1850K in this case. The mole fraction of the hard phase in the alloy that is nickel boride (Ni3B) is greater than 5 mole percent. In this case, the chemical components of the base material are extracted at 1200K, and the approximate The alloy has a liquidus temperature of 140 0 K, which makes the material highly suitable for gas atomization. Ni3B is It is a hard phase and exists at a mole fraction of 66% at 1300 K. The chemical composition of the matrix is ​​33 The chemical composition of the base material of P76-X23 is P76-X23. It can be seen that the bulk chemical composition of P76-X23 is completely different from that of Monel. It is designed to have similar corrosion performance to the Monel 400 and is compatible with the P76-X23 The similarity to the base material 400 is 100%.

[0074] [Microstructure conditions] In some embodiments, an alloy can be described by its microstructural condition. In some embodiments, the alloy is characterized as meeting some of the microstructural criteria described. In some embodiments, the alloy may have all of the microstructural conditions described. can be characterized as satisfying

[0075] The first microstructural condition relates to the total measured volume fraction of ultrahard particles. For purposes of this disclosure, ultrahard The hardness of the grains is 1000 Vickers or more (or about 1000 Vickers or more). The total concentration of ultrahard particles can be defined as 1000 Vickers (or about 1000 Vickers) hardness and 1500K (or It can be defined as the total mole percent of all phases that are thermodynamically stable at temperatures above 1500 K. In some embodiments, the alloy comprises at least 3% by volume (or at least about 3 % by volume, at least 4% by volume (or at least about 4% by volume), at least 5% by volume (or at least about 5% by volume), at least 8% by volume (or at least about 8% by volume), %), at least 10% by volume (or at least about 10% by volume), at least 12% by volume % (or at least about 12% by volume), or at least 15% by volume (or less at least about 15% by volume of ultra-hard particles, at least 20% by volume (or at least about 20% by volume % by volume of ultra-hard particles, at least 30% by volume (or at least about 30% by volume) of ultra-hard particles Hard particles, at least 40% by volume (or at least about 40% by volume) of ultrahard particles, At least 50% by volume (or at least about 50% by volume) of ultra-hard particles, or any other The ultrahard particles may range anywhere between these values.

[0076] In some embodiments, the ultra-hard particle fraction may vary depending on the intended alloy processing. For example, in a thermal spray alloy, the hard particle fraction is 40-60% by volume (or about 40-60% by volume). ) Laser, plasma transferred arc, or other wire welding. In alloys used for welding by application, the hard particle phase fraction is 15-30% by volume. (or about 15 to about 30% by volume).

[0077] The second microstructural condition relates to the fraction of hypereutectic separated hard phases in the alloy. When used in this context, separation means that a particular separated phase (e.g., spherical or partially spherical particles) separates from other hard particles. For example, a separate phase may be 100% surrounded by the matrix phase. This can result in low-toughness "bridges" that initiate cracks across the microstructure. This can be contrasted with rod-like phases which may form long needles that act as magnets.

[0078] To reduce the alloy's susceptibility to cracking, a separate hypereutectic phase is formed rather than a continuous grain boundary phase. In some embodiments, the separated hypereutectic hard phase is The total hard phase fraction in gold is 40% by volume or more (or about 40%), % by volume (or about 45%) or more, 50% by volume (or about 50%) or more, 60% by volume ( or about 60%) or more, 70% by volume (or about 70%) or more, 75% by volume (or about 75%) or more, or 80% by volume (or about 80%) or more, or any value therebetween It can be any range between.

[0079] The third microstructural condition is related to increasing the corrosion resistance of the alloy. To increase corrosion resistance, the total weight percentage of chromium and molybdenum in the base material can be increased. It may be useful to determine the total weight percent of chromium and molybdenum in the base material. In some embodiments, an energy dispersive spectrometer (EDS) was used to measure the The total content of chromium and molybdenum in above), 18% by weight or more (or about 18% by weight or more), 20% by weight or more (or about 20% by weight or more) % by weight or more), 23% by weight or more (or about 23% by weight or more), 25% by weight or more (or about 25% by weight or more), 27% by weight or more (or about 27% by weight or more), or 30% by weight or more % by weight or more (or about 30% by weight or more), or any range therebetween. It is possible.

[0080] The fourth microstructural condition is, for example, Inconel 625, Inconel 686, or M The alloy's base metal chemistry is compared to that of known alloys such as ionel. To measure the components, an energy dispersive spectrometer (EDS) was used. In this case, the base material similarity is 50% (or about 50%) or more, 55% (or less) of the known alloy. 55% or more, 60% (or about 60%) or more, 70% (or about 70%) or more Above 80% (or about 80%) or more, 85% (or about 85%) or more, or 90 % (or about 90%) or more, or any range between any of these values.

[0081] The parent material approximation is similar to that described in the thermodynamic conditions section and is calculated in this case The difference between "base material chemical composition" and "base material similarity" is that the chemical composition is similar to that found in a solid solution of the nickel base material. The actual values ​​of Cr, Mo, or other elements that can be accepted are the approximate values ​​for good resistance. How closely the nickel base metal of a designed alloy matches the chemical composition of known alloys that have corrosion properties For clarity, the value is taken from Inconel et al. Since the known alloys are single-phase alloys, the alloy composition is effectively the base metal composition, and all alloying elements are The elements are found in solid solution. The alloys described herein that precipitate hard phases for wear resistance is not the case.

[0082] Figure 3 shows the SEM image of the microstructure of P82-X6 when prepared by PTA welding. In this case, the alloy was prepared as a powder mixture for the experiment. At 500K, the precipitates exhibited separate niobium carbide precipitates with a volume fraction of more than 5%. 02 shows hypereutectic hard phase that is more than 50% of the total hard phase in the alloy, and 303 shows Inc This indicates a base material that has a similarity to the base material of over 60% when compared with carbide 625. The precipitates are classified into two types, segregated (larger size) and eutectic, both of which contribute to the total hard phase content. In this example, the hard phase in the form of a separation is The carbide fraction exceeds 50 volume %.

[0083] [Performance Conditions] In some embodiments, the hardfacing layer is a PTA cladding or laser - Made by a weld build-up process, including but not limited to cladding.

[0084] In some embodiments, the alloys may have a number of advantageous performance properties. In some embodiments, the alloy has the following characteristics: 1) high wear resistance; 2) ease of laser cladding processing; 2) When welded by welding or other welding methods, there is minimal or no cracking; and It may be advantageous to have one or more of the following properties: The abrasion resistance of an alloy can be quantified using the ASTM G65A dry sand abrasion test. The crack resistance of a material can be quantified using a dye penetration test on the alloy. The corrosion resistance of the alloys shall be quantified using ASTM G48, G59, and G61 tests. All of the above ASTM tests are incorporated herein by reference in their entirety. can be.

[0085] In some embodiments, the hardfacing layer is 250 mm 3 Less than (or about 2 50mm 3 Less than 100mm 3 Less than (or about 100 mm 3 Less than 30mm 3 less than (or about 30 mm 3 Less than 20mm 3 Less than (or about 20 mm 3 (less than) A May have STM G65A wear loss.

[0086] In some embodiments, the hardfacing layer comprises 5 cracks per square inch, 4 cracks per square inch, 3 cracks per square inch 2 cracks per square inch, 1 crack per square inch, or 0 cracks per square inch, or may generate any range between any of those values. This is a line of surface cracking without separating into separate pieces.

[0087] In some embodiments, the hardfacing layer is made of 50% (or Approximately 50%) or more, 55% (or approximately 55%) or more, 60% (or approximately 60%) or more, 70% (or about 70%) or more, 80% (or about 80%) or more, 85% (or About 85%) or more, 90% (or about 90%) or more, 95% (or about 95%) or more, 98% (or about 98%) or more, 99% (or about 99%) or more, or 99.5 % (or about 99.5%) or greater, or any range between any of these values. may have the following structure:

[0088] Corrosion resistance is complex and may depend on the corrosive medium used. The corrosion rates of the alloy embodiments are approximately equal to the corrosion rates of the comparative alloys that they are intended to replicate. For example, Inconel 625 can be used in certain corrosive media. At a corrosion rate of 1mpy (mils per year), P82-X6 provides 80% corrosion resistance. The corrosion resistance may be 1.25 mpy or less so as to obtain the above-mentioned desired corrosion resistance. It is specified as 1 / corrosion rate.

[0089] In some embodiments, the alloy is placed in an environment of 28% CaCl2 electrolyte, pH=9.5. In some embodiments, the corrosion rate is less than or equal to 1 mpy. In an embodiment, the alloy is 0. 6 mpy or less (or about 0.6 mpy or less). In terms of morphology, the alloy exhibited a 0.4% CaCl2 electrolyte at pH=9.5. mpy or less (or about 0.4 mpy or less).

[0090] In some embodiments, the alloy is subjected to 3.5 h heat treatment according to G-59 / G-61 for 16 h. % sodium chloride solution is less than 0.1 mpy (or less than about 0.1 mpy) In some embodiments, the alloy may be G-59 / G-6 In a 3.5% sodium chloride solution for 16 hours according to 1, the The alloy may have a corrosion resistance of less than about 0.08 mpy.

[0091] In some embodiments, the hardfacing layer is sprayed by high velocity fuel (HVOF) thermal spraying. The material may be fabricated by a thermal spray process, including but not limited to.

[0092] In some embodiments, the hardness of the coating is 650 (or about 650) Vickers or greater. In some embodiments, the hardness of the thermal spray process can be 700 (or about 70 0) Vickers or higher. In some embodiments, the hardness of the thermal spray treatment can be 9 00 (or about 900) Vickers or higher.

[0093] In some embodiments, the adhesion of the thermal spray coating is 7,500 (or about 7,500 In some embodiments, the adhesion of the thermal spray coating may be improved by increasing the pressure drop. The pressure may be 8,500 (or about 8,500) psi or greater. The adhesion of the thermal spray coating should be at least 9,500 (or about 9,500) psi. This can be done. EXAMPLES

[0094] [Example 1: PTA welding of P82-X6] Alloy P82-X6 is 53-80% alloy suitable for PTA and / or laser cladding. The alloy was gas atomized into powder with a particle size distribution of 150 μm. 2) 2.2kW laser power and 14L / min flow rate Laser cladding was performed using two parameter sets. In both cases Thus, the coating is intended to form a fine grain structure on the nickel matrix 402 as shown in FIG. The results show that the niobium / titanium carbide precipitates are well separated. The Vickers hardness at 300 grams force was calculated for parameter sets 1 and 2, respectively. The ASTM G65 test was performed with parameter sets 1 and 348, respectively. 1.58g (209mm 3 ) loss and 1.65g (200mm 3 ) loss I did.

[0095] [Example 2: HVOF spraying of P76-X23 and P76-X24] Alloys P76-X23 and P76-X24 have a hardness of 15-4 to make them suitable for HVOF thermal spray processing. The powders were gas atomized into 5 μm particle size distribution. Both powders consisted of nickel matrix phase and nickel boron phase. Although the id phases are thought to coexist as predicted by computational modeling, identification and Extremely fine-scale morphologies are formed that are very difficult to measure quantitatively.

[0096] As shown in FIG. 5, 501 is the gas atomized powder, and 502 is the coating of the resulting powder. The matrix and Ni boride phase 504 (e.g., eutectic nickel in gas-atomized powder) In addition to the nickel / nickel boride structure, the P76-X24 alloy also contains finely divided particles. Chromium boride precipitates 503 also form as predicted by the model.

[0097] 505 is a primary nickel / nickel boride eutectic structure for HVOF thermal spray coatings. 506 indicates an area with many chromium boride precipitates in the coating. Indicates the area.

[0098] Both alloys were HVOF sprayed to a coating thickness of approximately 200-300 μm, resulting in a dense coating. The Vickers hardness of the coating at 300 grams force was The scores for P76-X23 and P76-X24 were 693 and 726, respectively. Adhesion testing of P76-X24 resulted in adhesion failure of up to 9,999 psi, while P76-X24 failed at 9,576 and 75% adhesion and 25% adhesion failure in two tests up to 9,999 psi. ASTM G65A (converted from ASTM G65B) test is P76-X2 4 is 87mm 3 The ASTM G65A test used 6,000 revolutions and Method B uses 2,000 RPM and is typically used for thin coatings such as thermal spray coatings. Used.

[0099] P76-X24 was tested in 28% CaCl2 electrolyte, pH=9.5, and had a resistance of 0.4mpy In comparison, cracked hard chrome had a measured corrosion rate of 1.06mpy in a similar environment. Hard Cr is used in a variety of applications requiring both corrosion and abrasion resistance. In some embodiments, the HVOF coating is used as a suitable coating. The alloy in the form of a ring is galvanically sealed at 1mpy in a 28% CaCl2 electrolyte, pH=9.5 environment. In some embodiments, the HVOF coating morphology results in the following corrosion rates: Gold corrodes at less than 0.6mpy in a 28% CaCl2 electrolyte with a pH of 9.5. In some embodiments, the HVOF coating may provide a high velocity. The alloy corrodes at less than 0.4 mpy in a 28% CaCl2 electrolyte, pH=9.5. In some embodiments, the morphology of the HVOF coating can be The alloy provides an impermeable coating in ECP (electrochemical potential) tests. .

[0100] [Example 3: HVOF spraying of WC / Cr3C2, Ni alloy matrix mixture] 80 wt% WC / Cr3C2 (50 / 50 vol%) mixed with 20 wt% Monel The mixture was agglomerated to 15-45 μm for thermal spray processing and sintered. The ting has a 300 g Vickers hardness of 946, as shown in Figure 6, and a hardness of 0.43 The HVOF coating formed a dense coating with a measured porosity of 100%. Approximately 12 mm at 5 A 3 FIG. 6 shows the mass loss of the WC / C in Example 3. Agglomerated and sintered powder of r3C2+Ni alloy, specifically 80% mixed with 20% Monel by weight. Shown is an SEM image of a mixture of WC / Cr3C2 (50 / 50 volume %) by weight.

[0101] [Example 4: Comparison of P82-X13, 14, 15, 1 8, 19 Welding Research] Several studies of different carbide contents and morphologies in comparison with Inconel 625. Alloys were evaluated and welding studies were performed. All alloys in the study were Inconel6 25, which is quantified by the matrix similarity, and 0% is equivalent to a base material that closely resembles the bulk composition of Inconel 625. All alloys were laser welded in three overlapping layers to test for cracks and To test other properties, two-pass welds of each alloy were plasma transferred arc welded. This is what I created. [Table 2]

[0102] P82-X18 represents an embodiment of this disclosure that yields favorable results at the conclusion of this study. P82-X18 is significantly more durable than Inconel 625 in both PTA and laser processing. Even with the increased hardness, no cracks were observed in the laser or PTA cladding samples. This apparently did not occur. P82-X18 was in the Inconel 625 alloy in both treatments. The general trend of increasing hardness is shown in Table 3. Surprisingly, however, the increase in hardness is similar for all tested alloys. Not all cases result in increased wear resistance. P82-X13, P82-X1 4, and P82-X15 are all harder and contain carbides, but are similar to Inconel The wear rate was higher than that of 625. This result was compared with the total carbide fraction and the alloy hardness. The discovery of advantageous carbide morphology when

[0103] Alloy P82-X18 meets the thermodynamic, microstructural, and performance criteria of this disclosure. P82-X18 is predicted to form 8.1 mol % isolated carbides. In fact, the formation of 8-12% segregated carbides occurred in the industrially relevant welding processes studied. This alloy is also predicted to form 9.9 mol% of grain boundary hard phase, and in fact, 10 The segregated carbide content is calculated based on the total carbide content in the alloy. This increase in the fraction of separated carbides is due to the increase in the total carbide fraction alone. Improves wear resistance beyond that which may be expected from [Table 3] [Table 4]

[0104] The base material of P82-X18 was measured by energy dispersive spectroscopy, and Cr: 19-20 wt. The composition of the base material was thus: Cr: 2 0~23, Mo: 8~10, Nb+Ta: 3.15~4.15, Ni: remaining amount, typical It is very similar to, and to some extent overlaps with, the typical Inconel 625 product range. was tested in the G-48 ferric chloride immersion test for 24 hours and showed the same corrosion resistance as Inconel 625. P82-X18 was run for 16 hours according to the G-59 / G-61 ASTM standard. Corrosion tests were performed in a 3.5% sodium chloride solution at 0.075 to 0.078mpy( The corrosion rate (mils per year) was measured.

[0105] In some embodiments, 3.5% sodium chloride for 16 hours according to G-59 / G-61 The corrosion rate of the material measured in thorium solution is less than 0.1 mpy. In one embodiment, the gel is immersed in 3.5% sodium chloride for 16 hours according to G-59 / G-61. The corrosion rate of the material measured in liquid is less than 0.08mpy.

[0106] In some embodiments, the alloys disclosed herein, such as P82-X18, are Nickel or other common materials as the metal component in metal matrix composites (MMCs) A typical example of a type of MMC is 60% WC, 60% N In this example, P82-X18 is used, which contains 60% WC by weight and P82-X18 40% by weight type MMC can be obtained. Various carbide ratios and carbide types are available.

[0107] Example 5: HVOF spray study of P82-X18 P82-X18 was sprayed using a hydrogen-fueled HVOF process. The resulting coating It has a bond strength of 10,000 psi, a Vickers hardness of 700HV300, and a ASTM G65B Mass Loss (10.4.6g / mm 3 volume loss) Ta.

[0108] Example 6: HVOF spray study of 30% NiCu agglomerated and sintered materials. Composition 1) 65~75% WC / Cr3C2+25~35% NiCu alloy and composition 2) Agglomeration and sintering process according to 65~75%Cr3C2+25~35%NiCu alloy Two powders were produced by the process. The first mixture was characterized by agglomerated and sintered particles. The total volume fraction is 65-75% carbide, and the remaining portion is NiCu metal alloy. The carbide content of the particles is itself a mixture of both WC and Cr3C2 carbide types. In some embodiments, the WC / Cr3C2 ratio is between 0 and 100 by volume. In some embodiments, the WC / Cr3C2 ratio is about 0.33 to 3 by volume. In some embodiments, the WC / Cr3C2 ratio is about 0.25 to 5 by volume. In this state, the WC / Cr3C2 ratio is about 0.67 to 1.5. The composition of the NiCu alloy is Cu: 20-40 wt%, each containing less than 3 wt% of other common impurities, preferably Preferably, Cu: 25 to 35% by weight, more preferably Cu: 28 to 34% by weight, the balance being nickel. It is.

[0109] Both powders were thermally sprayed by HVOF processing to form coatings which were then tested. Coatings made from powder 1 and powder 2 were dissolved in 28% CaCl2 electrolyte, pH=9. The corrosion rates in the five solutions were 0.15mpy and 0.694mpy, respectively. Powder 1 and the coating made from powder 2 was impermeable as measured by the ECP test. The coatings made from powder 1 and powder 2 were, respectively, ASTM G65A 11.3mm in 3 and 16.2mm 3 The wear volume loss of Powder 1 and Powder 2 was The coatings made from these materials have microhardness values ​​of 816HV300 and 677HV300, respectively. Coatings made from both powders exhibited weld strength values ​​in excess of 12,500 psi. It was the strength of the garment.

[0110] [Application] The alloys described in this disclosure can be used in a variety of applications and industries. Some non-limiting uses include: Examples of applications include surface mining applications, marine applications, power industry applications, oil and gas applications, and glass applications. Includes manufacturing applications.

[0111] Surface mining applications include the following components and coatings: Slurry pipes Wear resistant sleeves and / or wear resistant hardfacings of lines, pump housings or Mud pump components including impellers or hard facings of mud pump components, chute blocks Feed chute members including hard facings of rotary brakes or chute blocks Including but not limited to car screens, banana screens, and shaker screens Separating screens that are not used, liners for autogenous and semi-autogenous grinding mills, drilling tools and drilling Wear for hardfacing of tools, bucket truck and dump truck liners Plates, heel blocks of mining shovels and hard facings of heel blocks, Hard facing for radar blades and grader blades, stacker reclaimers, Typical wear packages for sizer crushers, mining elements and other crushing elements.

[0112] From the above, it is apparent that an inventive nickel-base hardfacing alloy and method of use are disclosed. It will be understood that some elements, techniques, and aspects are described with a certain degree of detail. However, certain of the above-described embodiments may be modified without departing from the spirit and scope of the present disclosure. It will be apparent that many variations in design, construction and method may be made.

[0113] Certain features that are described in this disclosure in the context of separate embodiments may also be combined in a single embodiment. Alternatively, various features that are described in the context of a single embodiment may be implemented in combination. The embodiments may be implemented separately or in any suitable subcombination. Although the features may be described above as acting in certain combinations, one or more of the described combinations may Features may, in some cases, be removed from a combination and the combination may be classified as a subcombination or a subcombination of a subcombination. It can be described as a transformation.

[0114] Also, the methods may be shown in the figures or described in the specification in a particular order, but may be any order that is desired. It is not necessary that such methods be performed in the particular order or sequential order presented to achieve the results shown. It is not necessary to carry out all the steps. Any other steps not shown or described are not included. One or more additional methods may be incorporated into the exemplary methods and processes. before, after, simultaneously with, or during any of the methods described. Additionally, the methods may be rearranged or sequenced in other embodiments. It is also understood that in all implementations, the separation of the various system components in the above described embodiments is intended to be The embodiments should not be understood to require such separation, and in general, the described configurations Elements and systems can be integrated together in a single product or packaged into multiple products. It should be understood that other embodiments are within the scope of this disclosure. .

[0115] Unless specifically stated or understood within the context in which it is used, "can" Conditional language such as "could," "may," or "may" generally refers to a given implementation. It is understood that the embodiments may or may not include certain features, components, and / or steps. Thus, such conditional language is intended to include features, components, and Generally, the indication that the step or steps are somehow required in one or more embodiments is omitted. Not intended.

[0116] Unless specifically stated, conjunctions such as "at least one of X, Y, and Z" A continuation phrase means that an item, term, etc. can be either X, Y, or Z. Therefore, such transitional phrases are understood in the context of their general use as if they were The embodiment further comprises the presence of at least one X, at least one Y, and at least one Z. No suggestion that it is required is generally intended.

[0117] As used herein, the terms "approximately," "about," "generally," and "substantially" As used herein, the term "compound" refers to a compound that performs a desired function or achieves a desired result. represents a value, amount, or characteristic that is approximately equal to the stated value, amount, or characteristic. The terms "about," "generally," and "substantially" mean any amount greater than or equal to 10% of the stated amount. It can refer to an amount of 5% or less, 1% or less, 0.1% or less, or 0.01% or less. If the amount of the above is zero (e.g., none, nothing), the above ranges will not be considered as specific ranges. can be within a certain percentage of the value. For example, Weight / volume % or less, 5 weight / volume % or less, 1 weight / volume % or less, 0.1 weight / volume % or less , 0.01% by weight / volume or less.

[0118] Any particular features, aspects, methods, properties, characteristics, properties, attributes, structures, configurations, etc. relating to various embodiments may be used without departing from the spirit or scope of the present invention. The disclosure herein of any components, etc. may be used in all other embodiments shown herein. Furthermore, any of the methods described herein can be performed by carrying out the steps described. It will be appreciated that this may be implemented using any suitable device.

[0119] Although a number of embodiments and variations thereof have been described in detail, other modifications and uses thereof are contemplated. Methods for implementing the method will be apparent to those skilled in the art. Accordingly, various applications, modifications, materials, and Alternatives depart from the specific inventive disclosure herein or the scope of the claims. It is important to understand that this can be done from the perspective of the equivalent.

Claims

[Claim 1] Ni, 0.5% to 2% by weight of C; 10% to 30% by weight of Cr; 5.81 wt% to 18.2 wt% Mo; A raw material containing 2.38% by weight to 10% by weight of Nb+Ti.